2018
DOI: 10.1111/obr.12686
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss interventions for adults with overweight/obesity and chronic musculoskeletal pain: a mixed methods systematic review

Abstract: Worldwide prevalence of adult overweight and obesity is a growing public health issue. Adults with overweight/obesity often have chronic musculoskeletal pain. Using a mixed-methods review, we aimed to quantify the effectiveness and explore the appropriateness of weight loss interventions for this population. Electronic databases were searched for studies published between 01/01/90 and 01/07/16. The review included 14 randomized controlled trials that reported weight and pain outcomes and three qualitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 86 publications
(297 reference statements)
1
35
2
Order By: Relevance
“…Although obese patients had the least reduced pain intensity Post‐IMMPR, no BMI group reported a reduction large enough to reach the minimal clinically important difference. Consistent with our findings, two other research groups focused on morbidly obese patients receiving weight loss interventions, also reported lack of clinically significant reduction in pain intensity (Cooper, Ryan, et al., ; Dunlevy et al., ). In the normal weight group, the effect size was small, but this must be seen in the perspective that these patients represent a selection of patients with complex chronic pain conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Although obese patients had the least reduced pain intensity Post‐IMMPR, no BMI group reported a reduction large enough to reach the minimal clinically important difference. Consistent with our findings, two other research groups focused on morbidly obese patients receiving weight loss interventions, also reported lack of clinically significant reduction in pain intensity (Cooper, Ryan, et al., ; Dunlevy et al., ). In the normal weight group, the effect size was small, but this must be seen in the perspective that these patients represent a selection of patients with complex chronic pain conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Although our study did not indicate decreased body mass in the voluntary physical activity groups (Figure 2), a meta-analysis reported that body mass reduction promoted by physical activity or other interventions such as caloric restriction can contribute to pain reduction in humans with chronic musculoskeletal pain (Cooper L. et al, 2018). The contrast between these results may suggests that the effect of voluntary physical activity in preventing chronic pain susceptibility in mice, or pain reduction in humans with chronic pain, may also be mediated by differential gene expression related to neuroplasticity in the NAc, independent of body mass reduction, as was reported here.…”
Section: Biological Processescontrasting
confidence: 74%
“…A cross-sectional study from low-and middle-income countries showed that sedentary behavior is strongly related to obesity and chronic pain and suggested that interventions focusing on reducing sedentary behavior should be considered for these chronic conditions (Koyanagi et al, 2018). A recent study in adults with obesity or overweight demonstrated that weight loss interventions such as voluntary physical activity promoted significant pain reduction (Cooper L. et al, 2018), adding to the known effects and growing literature relating the benefits of increased physical activity for treatment of chronic pain (Geneen et al, 2017;Lima et al, 2017a,b) and obesity (Paley and Johnson, 2016). However, studies investigating the interactions between high-fat diet (HFD), sedentary behavior, voluntary physical activity in chronic pain susceptibility are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe pain lost less weight than those with none-to-moderate pain during a weight management program, suggesting severe pain impeded their weight loss [ 18 , 19 ]. Unfortunately, current clinical practice is more likely to treat pain and excess weight as separate issues [ 11 , 20 ]. The complexity of managing each condition independently means that some other factors need to be considered.…”
Section: Introductionmentioning
confidence: 99%